Computational studies of pyrite-and marcasite-type structures; OsAs2, OsS2, RuAs2, and RuS2 - Rapetsoa, Mamphule Johannes (My University, 2009)
Calculations were carried out on transition-metal sulphides (TMS) and transitionmetal arsenides (TMA), in both pyrite- and marcasite-type structures, using planewave (PW) pseudopotential methods within density functional theory (DFT) in the local density approximation (LDA). The structural, electronic and optical properties for both pyrite- and marcasite-type structures (naturally occurring and converted) have been investigated. The equilibrium lattice parameters were investigated and are in good agreement with the experimental values. The heats of formation calculations predict that the naturally occurring pyrite- and marcasite-type structures are more stable than the converted ones. In particular, the calculated pyrite-type RuS2 compares well to the experimental value (with energy difference of 0.381 eV/atom). The bulk modulus and elastic properties were calculated. The predicted anisotropic ratio shows that the naturally occurring pyrite- and marcasite-type structures are more stable than the converted ones. Moreover, the electronic density of states and band structure calculations reveal that most compositions shows semiconducting behaviour except for the converted pyritetype structures, i.e OsAs2 and RuAs2 where a metallic behaviour was observed. The electronic charge density and charge density difference show charge accumulation on bonding atoms, predicting the charge gain/ loss and nature of bonding to be covalent/ weak ionic between the atoms. Lastly, optical properties are computed at equilibrium and predict that naturally occurring structures have lower absorption and reflectivity than the converted structures. At different pressures ranging from -10 GPa to 10 GPa, the absorption and reflectivity spectra show a shift from the 0 GPa spectrum for all the structures
Thesis (MSc. (Physics)) --University of Limpopo, 2009
Keywords: Computational studies; Pyrite type structures; Marcasite type structures; 541.0968; Sulphide minerals